Time-dependent deformation and cracking behaviour of FRC beams. (1st October 2022) - Watts, M.J.; Amin, A.; Gilbert, R.I.
Highlights: Results of a 2 year experimental campaign on FRC beams is presented. Fibres significantly reduce deformation immediately after load is applied to RC. The time dependent deformation of FRC beams is greater than RC beams. Steel fibres resulted in finer crack widths than polypropylene FRC. Previously developed models show good agreement with the experimental results. Abstract: The serviceability performance of structural concrete can be significantly improved through the addition of steel or polypropylene fibres. These benefits are well known in industry and practice. Consequently, several national codes of practice contain well established procedures to predict the strength and short-term serviceability behaviour of fibre reinforced concrete (FRC) structures. However, expressions capable of predicting the long-term serviceability behaviour of FRC are either not included or provide limited guidance. This limits the full utilisation of FRC in design practice. In the context of increasing FRC structural application, an experimental program has been carried out aiming to quantify the time-dependent deformation and cracking behaviour of FRC flexural members. Six large-scale specimens with varying fibre types (either no fibres, steel or polypropylene fibres), varying geometries and varying longitudinal reinforcement ratios were constructed and subjected to sustained uniformly distributed loads. The deformation and cracking behaviour of the specimens were continuously recorded. A complete suite of material characterisation tests was conducted in conjunction with the large-scale testing. The results of the testing indicate that the addition of the dosage of steel fibres used in this study to concrete significantly improves the time-dependent behaviour of determinate concrete structures by reducing long term deformations and the severity of cracking. The addition of the adopted dosage of polypropylene fibres for specimens tested in this study had a marginal effect on the time-dependent behaviour. Models previously developed by the authors are compared to the test data and are shown to correlate well.